2009
DOI: 10.1088/1742-5468/2009/02/p02056
|View full text |Cite
|
Sign up to set email alerts
|

A scale-invariant model for snow slab avalanches

Abstract: On the basis of the evidence of fractality reported in the literature as regards snow material and snow avalanches, the paper introduces a statistical model for the natural release of slab avalanches characterized by the differing cohesion of the snow cover at different scales. Under the hypothesis of scale invariance of shear strength, this model can be used to estimate the stability of snow slopes of different types, and to examine whether defects can propagate from the microscale (cohesion and friction) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…While qualitatively their results showed similar trends for the evolution of the knock-down function with CV, quantitatively the results were very different. Chiaia and Frigo [2009] also used a related approach based on a scale-invariant fractal model to evaluate the conditions of failure of a slab-WL system taking into account a random distribution of the shear strength. They showed, in particular, how complex local interactions and failures at small scales may lead to catastrophic failure at the macroscopic scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While qualitatively their results showed similar trends for the evolution of the knock-down function with CV, quantitatively the results were very different. Chiaia and Frigo [2009] also used a related approach based on a scale-invariant fractal model to evaluate the conditions of failure of a slab-WL system taking into account a random distribution of the shear strength. They showed, in particular, how complex local interactions and failures at small scales may lead to catastrophic failure at the macroscopic scale.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to investigate slope stability and avalanche release size, measured variations in snow properties have been used as input for numerical models of slab-weak layer systems [Failletaz et al, 2004;Zaiser, 2004, 2007;Chiaia and Frigo, 2009;Gaume et al, 2012Gaume et al, , 2013a. By coupling results of a mechanical model accounting for variations in the mechanical properties of the weak layer with observed snowfall GAUME ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we argue that snow density is a function of the scale and the probability to find large defects (e.g. superweak zones in a weak layer) increases with the dimension of the snow grain, as for example providing more intrinsic brittleness for large snow slopes [32,33]. Numerical results reported…”
Section: Menger Sponge Modelmentioning
confidence: 78%
“…Various mechanical models that have been used to address the dry snow slab avalanche release problem focused on weak layer failure: e.g. crack models inspired by the over-consolidated clay theory (McClung, 1979), cellularautomata models (Fyffe and Zaiser, 2004), fibre-bundle model (Reiweger et al, 2009), physical-statistical models (Chiaia and Frigo, 2009), multiple finite element method, FEM (Stoffel, 2005;Podolskiy et al, 2013), and analytical and empirical models (Zeidler and Jamieson, 2006). Recent studies, based on FEM with interfacial constitutive laws for weak layers, have shown that one of the key uncertainties in avalanche forecasting, spatial heterogeneity of weak layers, can be treated by statistical methods and that its importance is reduced for greater snow slab depths (Gaume, 2012;Gaume et al, 2012Gaume et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%